Viscosity and density measurements on liquid n-tetradecane at moderately high pressures - Santos, Tânia V. M. (2017)
The main aim of the work is to study the viscosity and density of compressed normal tetradecane in the region of pressures from saturation to 10 MPa, where the available literature data are scarce. New measurements of the viscosity of n-tetradecane (n-C14) along eight isotherms in the range (283–358) K and at pressures up to 70 MPa, have been performed using the vibrating wire technique in the forced mode of operation. Density measurements have also been performed along nine isotherms in the temperature range from (283 to 373) K and pressures from (0.1 to 70) MPa. The vibrating wire viscosity results were correlated with density, using a modified hard-spheres scheme. The root mean square (rms) deviation of the data from the correlation is less than 0.32% and the maximum absolute relative deviation is less than 1.0%. The expanded uncertainty of the present viscosity data is estimated as ±1.5% at a 95% confidence level. The density results were correlated with the temperature and pressure using a modified Tait equation. The expanded uncertainty of the present density data is estimated as ±0.2% at a 95% confidence level. The isothermal compressibility and the isobaric thermal expansion were calculated by differentiation of the modified Tait equation. The uncertainties of isothermal compressibility and the isobaric thermal expansion are estimated to be less than ±1.7% and ±1.1%, respectively, at a 95% confidence level. The results are compared with the available literature data.